Nephrotoxicity of Herbal Medicine and Its Prevention - Xu, Xiaofen; Zhu, Ruyi; Ying, Jialiang; Zhao, Mengting; Wu, Xin; Cao, Gang; Wang, Kuilong (Frontiers in Pharmacology, 2020)
Herbal medicine (HM) has been widely used to treat diseases for thousands of years and has greatly contributed to the health of human beings. Many new drugs have been developed from HM, such as artemisinin. However, artemisinin has adverse effects, such as renal toxicity. In 1993, a study conducted in Belgium reported for the first time that the root extracts of Aristolochia obliqua S. M. Hwang led to progressive interstitial renal fibrosis. The nephrotoxicity of HM has attracted worldwide attention. More than 100 kinds of HM induce renal toxicity, including some herbs, animal HMs, and minerals. This paper aimed to summarize the HM compounds that cause nephrotoxicity, the mechanisms underlying the toxicity of these compounds, biomarkers of renal injury, and prevention strategies. These findings provide basis for follow-up studies on the prevention and treatment of HM nephrotoxicity.